The Prevalence of Metabolic Syndrome in the Different Phenotypes of Polycystic Ovarian Syndrome - Tavares, Aleide; Rêgo Barros, Romualda Castro (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To evaluate the prevalence of metabolic syndrome (MetS) in the phenotypes of polycystic ovarian syndrome (PCOS).Methods This was a cross-sectional study involving 111 women aged between 18 and 39 years old diagnosed with PCOS, according to the Rotterdam Criteria, and grouped into four phenotypes: A: ovulatory dysfunction + hyperandrogenism + polycystic ovaries; B: ovulatory dysfunction + hyperandrogenism; C: hyperandrogenism + polycystic ovaries; D: ovulatory dysfunction + polycystic ovaries. To evaluate the presence of MetS, we measured serum triglyceride levels, HDL cholesterol, fasting blood glucose, blood pressure, and waist circumference.Results The prevalence of MetS found in this sample was 33.6%, and there was no statistically significant difference (p < 0.05) among the 4 phenotypes. However, phenotype D presented a significantly higher mean glucose level after fasting (93.6 mg/dL) and 2 hours after ingesting a solution with 75 g of anhydrous glucose (120 mg/dL), as well as the lowest mean level of high-density lipoprotein (HDL) cholesterol (44.7 mg/dL). The women in this group demonstrated a high prevalence of abdominal circumference ≥ 80 cm (68.2%), as well as the highest mean abdominal circumference (90.1 cm). Amongst the women with an abdominal circumference ≥ 80 cm, phenotype A increased approximately six-fold the chance of developing metabolic syndrome in relation to phenotype C.Conclusion The four phenotypes of PCOS demonstrated similar prevalence rates of metabolic syndrome; abdominal obesity presented a relevant role in the development of metabolic alterations, regardless of the phenotype.
Keywords: polycystic ovarian syndrome; phenotype; insulin resistance; metabolic syndrome; abdominal obesity